2014
DOI: 10.1155/2014/606870
|View full text |Cite
|
Sign up to set email alerts
|

Subchondral Bone Plate Thickening Precedes Chondrocyte Apoptosis and Cartilage Degradation in Spontaneous Animal Models of Osteoarthritis

Abstract: Osteoarthritis (OA) is the most common joint disorder characterised by bone remodelling and cartilage degradation and associated with chondrocyte apoptosis. These processes were investigated at 10, 16, 24, and 30 weeks in Dunkin Hartley (DH) and Bristol Strain 2 (BS2) guinea pigs that develop OA spontaneously. Both strains had a more pronounced chondrocyte apoptosis, cartilage degradation, and subchondral bone changes in the medial than the lateral side of the tibia, and between strains, the changes were alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 41 publications
0
31
0
Order By: Relevance
“…There is a need to better understand the complete spectrum of characteristics involved in this heterogeneous disease to improve characterization of knee OA sub-types. [39] In order to do so, we need to clearly document, define and analyze changes in cellular response,[40,41] extracellular matrix,[4244] tidemark and SCB [4548] that are important to the structure and function of cartilage. This is an important aspect from therapeutic perspective also, in order to improve the efficacy of the treatments, by identifying various possible OA sub-groups for targeted treatment procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to better understand the complete spectrum of characteristics involved in this heterogeneous disease to improve characterization of knee OA sub-types. [39] In order to do so, we need to clearly document, define and analyze changes in cellular response,[40,41] extracellular matrix,[4244] tidemark and SCB [4548] that are important to the structure and function of cartilage. This is an important aspect from therapeutic perspective also, in order to improve the efficacy of the treatments, by identifying various possible OA sub-groups for targeted treatment procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Zamli et al underlined that, unlike destabilization of the medial meniscus (DMM) mice model of OA, in which apoptosis was observed in the superficial zone (SZ) and middle zone (MZ), chondrocyte apoptosis in guinea pigs was confined to the deep zone of articular cartilage, perhaps reflecting a different mode of OA induction [122]. Zamli and co-workers further demonstrated that bone remodeling, via subchondral bone plate thickening, preceeded chondrocyte apoptosis and cartilage degradation [123]. …”
Section: Apoptosis In Chondrocytes and Osteoarthritis (Oa) Developmentioning
confidence: 99%
“…Furthermore, preserving subchondral bone integrity could be an alternative strategy, as subchondral bone plate thickening seems to be an early event in OA development, which preceded apoptosis of chondrocytes in a longitudinal animal study [123]. Also, therapies dedicated to the reduction of the catabolic phenotype of chondrocytes may protect against post traumatic OA [124].…”
Section: Targeting Chondrocyte Apoptosis For Oa Treatmentmentioning
confidence: 99%
“…Advantages of microCT include 3-dimensional visualization of the joint (vs. 2-dimensional views on histology), the ability to evaluate living specimens in a longitudinal fashion, and more sensitive detection of subtle bony lesions that tend to occur early in OA disease progression(26,27). As discussed further, below, it is advantageous that these multiplanar reconstructions of the intact organ can be made in an endless number of angles for complete evaluation of the entire joint.…”
Section: Discussionmentioning
confidence: 99%